Analisis Kinerja Keuangan Industri Mebel Di Kawasan Ampenan Pada Masa Pandemi Covid-19 Menggunakan Analisis Rasio (Studi Kasus Pada UD. Mebel Tinggar Jaya) - Muhammad Mulyaddin; I Nengah Arsana; Topan Siswanto (Kredibel: Jurnal Ilmiah Manajemen, 2025)
This research aims to analyze financial performance UD. Furniture Tinggar Jaya uses financial ratios, namely liquidity ratios, solvency ratios, profitability ratios before and during the covid-19 pandemic for the 2017-2022 period. So this research variable consistsof 3 (three) independent variables, namely liquidity ratio(X1), solvency variables (X2) and profitability ratio (X3) and financial performance (Y) . This type of research uses descriptive research. The data analysis technique used is financial ratio analysis. The result of this research show that there are fluctuations every year. From the liquidity aspect with current ratio and cash ratio indicators before and during the covid-19 pandemic for the 2017-2022 period UD. Furniture Tinggar Jaya is still in a stable conditionin paying off its current debtswith its current assets. From the solvency aspect with the debt to asset ratio and debt to equity ratio indicators before and during the covid-19 pandemic for the 2017-2022 period UD. Furniture Tinggar Jaya is also still in a stable condition in paying off its total debts with the total assets it owns. As for the profitability aspect with indicators of return on assets and return on equity before and during the covid-19 pandemic for the 2017-2022 periode UD. Furniture Tinggar Jaya is said to be in an unstable condition in gaining profits because the calculation results show it is below the industry standard average.